2017
DOI: 10.1111/eip.12428
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in antipsychotic naive African patients with severe mental illness in usual care

Abstract: There was a low prevalence and incidence of metabolic syndrome in this group of patients with a first episode of severe mental illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 51 publications
1
14
1
Order By: Relevance
“…Overall, we identified 31 eligible studies for inclusion in this meta‐analysis (Tables S3 and S4) (Arranz et al, ; Basoglu et al, ; Cai et al, ; Canan et al, ; Chang et al, ; Chen et al, ; Chen et al, ; Dasgupta, Singh, Rout, Saha, & Mandal, ; Enez Darcin, Yalcin Cavus, Dilbaz, Kaya, & Dogan, ; Fernandez‐Egea et al, ; Garcia‐Rizo et al, ; Garcia‐Rizo et al, ; Grover, Nebhinani, Chakrabarti, Avasthi, & Kulhara, ; Kavzoglu & Hariri, ; Keinanen et al, ; Leo et al, ; Misiak et al, ; Nyboe, Vestergaard, Moeller, Lund, & Videbech, ; Petrikis et al, ; Ryan et al, ; Saddichha, Manjunatha, Ameen, & Akhtar, ; Saloojee, Burns, & Motala, ; Sengupta et al, ; Spelman et al, ; Turan, Kesebir, & Suner, ; van Nimwegen et al, ; Venkatasubramanian et al, ; Wani et al, ; Wu et al, ; Yildirim et al, ; Zhang et al, ). Of these studies, one was conducted with patients who had a first episode mania (Turan et al, ), five were conducted with patients who had first episode depression (Canan et al, ; Chang et al, ; Garcia‐Rizo et al, ; Grover et al, ; Leo et al, ) and one was conducted with patients who had first episode mania or depression (Garcia‐Rizo et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, we identified 31 eligible studies for inclusion in this meta‐analysis (Tables S3 and S4) (Arranz et al, ; Basoglu et al, ; Cai et al, ; Canan et al, ; Chang et al, ; Chen et al, ; Chen et al, ; Dasgupta, Singh, Rout, Saha, & Mandal, ; Enez Darcin, Yalcin Cavus, Dilbaz, Kaya, & Dogan, ; Fernandez‐Egea et al, ; Garcia‐Rizo et al, ; Garcia‐Rizo et al, ; Grover, Nebhinani, Chakrabarti, Avasthi, & Kulhara, ; Kavzoglu & Hariri, ; Keinanen et al, ; Leo et al, ; Misiak et al, ; Nyboe, Vestergaard, Moeller, Lund, & Videbech, ; Petrikis et al, ; Ryan et al, ; Saddichha, Manjunatha, Ameen, & Akhtar, ; Saloojee, Burns, & Motala, ; Sengupta et al, ; Spelman et al, ; Turan, Kesebir, & Suner, ; van Nimwegen et al, ; Venkatasubramanian et al, ; Wani et al, ; Wu et al, ; Yildirim et al, ; Zhang et al, ). Of these studies, one was conducted with patients who had a first episode mania (Turan et al, ), five were conducted with patients who had first episode depression (Canan et al, ; Chang et al, ; Garcia‐Rizo et al, ; Grover et al, ; Leo et al, ) and one was conducted with patients who had first episode mania or depression (Garcia‐Rizo et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Of these studies, one was conducted with patients who had a first episode mania (Turan et al, ), five were conducted with patients who had first episode depression (Canan et al, ; Chang et al, ; Garcia‐Rizo et al, ; Grover et al, ; Leo et al, ) and one was conducted with patients who had first episode mania or depression (Garcia‐Rizo et al, ). Twenty‐four were conducted in patients with FEP (Arranz et al, ; Basoglu et al, ; Cai et al, ; Chen, Broqueres‐You, et al, ; Chen, Du, et al, ; Dasgupta et al, ; Enez Darcin et al, ; Fernandez‐Egea et al, ; Kavzoglu & Hariri, ; Keinanen et al, ; Misiak et al, ; Nyboe et al, ; Petrikis et al, ; Ryan et al, ; Saddichha et al, ; Saloojee et al, ; Sengupta et al, ; Spelman et al, ; van Nimwegen et al, ; Venkatasubramanian et al, ; Wani et al, ; Wu et al, ; Yildirim et al, ; Zhang et al, ). Among FEP studies, one study included patients with schizoaffective disorders (n = 4) in their patient group (n = 38) (Sengupta et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…After the removal of duplicates, 2473 abstracts and titles were screened. At the full-text stage, 112 were screened, 18 articles were included in a systematic review, 13 (De Hert et al, 2008;Effat et al, 2012;Enez Darcin, Yalcin Cavus, Dilbaz, Kaya, & Dogan, 2015;Garcia-Rizo et al, 2017;Grover, Nebhinani, Chakrabarti, Parakh, & Ghormode, 2012;Kraemer et al, 2011;Martín Otaño, Barbadillo Izquierdo, Galdeano Mondragón, Alonso Pinedo, & Querejeta Ayerdi, 2013;Medved, Kuzman, Jovanovic, Grubisin, & Kuzman, 2009;Owiredu, Osei, Amidu, Appiah-Poku, & Osei, 2012;Saddicha, Ameen, & Akhtar, 2007;Sahpolat & Ari, 2021;Saloojee, Burns, & Motala, 2018;Srivastava, Bhatia, & Sharma, 2018) articles were included in the main statistical analyses (prevalence of MetS in drug naïve, 0 days of antipsychotic medication) (Fig. 1) and an additional five studies that included up to 47 days were considered for the supplementary sensitivity analysis (see below).…”
Section: Search Resultsmentioning
confidence: 99%
“…We found that studies in Africa have the highest variability between their prevalence. Only two studies were performed in the Afro-descendant population, from Ghana and South Africa (Owiredu et al, 2012;Saloojee et al, 2018). We conducted sensitivity analysis removing those studies and we found changes in the overall prevalence from 13.2% to 16%.…”
Section: Ethnicity and Geographical Locationmentioning
confidence: 98%
See 1 more Smart Citation